1998
DOI: 10.1021/bi981200e
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Mechanism of HIV-1 Resistance to 3‘-Azido-3‘-deoxythymidine (AZT):  Increased Polymerization Processivity and Enhanced Sensitivity to Pyrophosphate of the Mutant Viral Reverse Transcriptase

Abstract: The multiple mutations associated with high-level AZT resistance (D67N, K70R, T215F, K219Q) arise in two separate subdomains of the viral reverse transcriptase (RT), suggesting that these mutations may contribute differently to overall resistance. We compared wild-type RT with the D67N/K70R/T215F/K219Q, D67N/K70R, and T215F/K219Q mutant enzymes. The D67N/K70R/T215F/K219Q mutant showed increased DNA polymerase processivity; this resulted from decreased template/primer dissociation from RT, and was due to the T2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
353
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(366 citation statements)
references
References 41 publications
11
353
1
1
Order By: Relevance
“…This resistance mechanism has been termed NRTI discrimination. The second mechanism involves the selective removal of the chain-terminating NRTI-MP from the prematurely terminated DNA chain (1,21). This mechanism has been termed NRTI excision.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This resistance mechanism has been termed NRTI discrimination. The second mechanism involves the selective removal of the chain-terminating NRTI-MP from the prematurely terminated DNA chain (1,21). This mechanism has been termed NRTI excision.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize that this putative interaction between K65 and E70 may alter the location of K65, thereby affecting NRTI-TP incorporation. HIV-1 RT has the innate capacity to unblock NRTI-MPterminated primers in the presence of physiological concentrations of ATP or PPi (1,22). Biochemical studies show that TAMs confer resistance to AZT and other NRTI by accelerating the rate at which the terminal AZT-MP (or other NRTI-MP) is removed through phosphorolytic cleavage (3,21).…”
Section: Discussionmentioning
confidence: 99%
“…The other class of resistance mechanism involves repair (or unblocking) of the analog-terminated DNA chain, using PP i or a nucleoside 5Ј-NTP as a cosubstrate for the pyrophosphorolysis reaction (4,7). Mutations in RT such as M41L, D67N, K70R, L210W, T215Y/F, or K219Q/E/N (referred as thymidine analog-associated mutations) increase the unblocking activity in the case of resistance to AZT and d4T (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Nucleoside analogue inhibitors of the retroviral reverse transcriptase (NRTIs) 1 represent important components in currently used drug regimens to treat infection with the human immunodeficiency virus, type 1 (HIV-1). 3Ј-Azido-3Ј-deoxythymidine (zidovudine or AZT), 2Ј,3Ј-dideoxyinosine (didanosine), and (Ϫ)-␤-L-2Ј,3Ј-dideoxy-3Ј-thyacytidine (lamivudine) are prominent members of this class of compounds.…”
mentioning
confidence: 99%
“…NRTIs are intracellularly phosphorylated and act as chain terminators. Previous biochemical studies have shown that the incorporated chain terminator can be removed from the primer terminus through phosphorolytic cleavage in the presence of either pyrophosphate (PP i ) (1) or in the presence of ribonucleotide triphosphates (NTPs) (2), which were shown to act as pyrophosphate donors. Increasing evidence suggests that the latter reaction pathway provides an important mechanism for HIV resistance to AZT and, to a certain degree, also to other NRTIs (3)(4)(5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%